4‐Hydroxyphenylpyruvate Dioxygenase Inhibitors in Combination with Safeners: Solutions for Modern and Sustainable Agriculture. Issue 36 (26th July 2013) - Ahrens, Hartmut; Lange, Gudrun; Müller, Thomas; Rosinger, Chris; Willms, Lothar; van Almsick, Andreas
Abstract Inhibitors of 4‐hydroxyphenylpyruvate dioxygenase (HPPD) prevent plant carotenoid pigment formation, which in turn leads to chlorophyll degradation. This "bleaching" herbicide mode of action provides weed‐control products for various crops, such as rice, corn, and cereals. Combinations with suitable safeners allow the full exploitation of the potential of this compound class to selectively control major weed problems, including rapidly increasing cases of resistance against other important herbicide classes.